Test–Retest Reliability of the 25-item version of Wender Utah Rating Scale. Impact of Current ADHD Severity on Retrospectively Assessed Childhood Symptoms. Issue 7 (May 2021) - Lundervold, Astri J.; Vartiainen, Henna; Jensen, Daniel; Haavik, Jan
Objective: To investigate test–retest reliability of the 25-item version of Wender Utah Rating Scale (WURS-25) and factors influencing retrospective reports of childhood behavior in adults with ADHD.Method: Eighty-five adults with ADHD and 189 controls completed the WURS-25 and the adult ADHD Self-Rating Scale (ASRS) at two time points (mean interval = 7 years) and provided information about dyslexia, somatic, and psychiatric disorders.Results: The correlation between WURS-25 scores at the two time points was strong, and reports from 60% of the adults with ADHD showed no change in severity level. Reports on the WURS-25 were positively associated with current ADHD symptoms at both time points and the presence of dyslexia and mood disorders, with the strongest association found among adults reporting the most severe WURS-25 score.Conclusion: Although our study showed an acceptable test–retest reliability of WURS-25, the substantial contribution from current ADHD symptoms to the WURS scores emphasizes the importance of collateral information from family members and others who knew the adult in childhood.